2014
DOI: 10.1016/j.jcf.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of matrix metalloproteinase (MMP)-9 in cystic fibrosis

Abstract: These associations further justify investigation of MMP-9 and TIMP-1 as biomarkers for short- to medium-term FEV1 decline and mortality in patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…Increases in the MMP-9/TIMP-1 ratio were predominantly due to increases in total MMP-9, with an insufficient increase in TIMP-1 release observed. A recent study reported that plasma TIMP-1 concentration was adversely associated with survival in adults [15]. These counterintuitive findings suggest that the innate regulatory mechanisms of MMP-9 fail to respond correctly in the lung, and, although not assessed in this study, neutrophil elastase mediated degradation of TIMP-1 may contribute to elevated MMP/TIMP-1 in children with elevated neutrophil elastase in BALF [13,18].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Increases in the MMP-9/TIMP-1 ratio were predominantly due to increases in total MMP-9, with an insufficient increase in TIMP-1 release observed. A recent study reported that plasma TIMP-1 concentration was adversely associated with survival in adults [15]. These counterintuitive findings suggest that the innate regulatory mechanisms of MMP-9 fail to respond correctly in the lung, and, although not assessed in this study, neutrophil elastase mediated degradation of TIMP-1 may contribute to elevated MMP/TIMP-1 in children with elevated neutrophil elastase in BALF [13,18].…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, detection of MMPs is indicative of airway disease, with elevated MMP-9/TIMP-1 ratios linked to worse outcomes in cystic fibrosis across a number of studies [12,13,15,28]. In this assessment of 64 BALF samples taken when children were free of exacerbation, but exhibiting a range of disease severity, the concentrations of MMP-2, MMP-9 and TIMP-1 reported are similar to the minimal data available in children with cystic fibrosis aged <6 years [14,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in glioma stem cells also demonstrated that TLR2 up-regulates MMP2 expression (18). MMP9 is predominantly produced by monocytes/ macrophages that abound in sites of chronic inflammation, such as periodontal disease, in which the connective tissue degradation by MMP9 is considered to trigger the disease pathology (24). MMP9 is also essential for initiating the osteoclastic resorption process by removing the collagenous layer from the bone surface before demineralization can start (14).…”
Section: Discussionmentioning
confidence: 99%
“…54 Plasma MMP-9 levels were elevated in CF patients and indirectly associated with percent predicted FEV 1 and rate of FEV 1 decline. Plasma TIMP-1 levels were inversely associated with mortality.…”
Section: Mmp Levels In Cf Blood Samplesmentioning
confidence: 89%